Effect of organic compost and inorganic nitrogen fertigation on spinach growth, phytochemical accumulation and antioxidant activity - R.M.A. Machado; I. Alves-Pereira; D. Lourenço; R.M.A. Ferreira (Heliyon, 2020)
The aim of this study was to evaluate the effect of the addition of organic compost in combination with the inorganic nitrogen fertigation on growth, phytochemical accumulation, and antioxidant activity of spinach (Spinacia oleracea L. cv. Manatee). Soil blocked spinach seedlings (six seedlings per block), three blocks per pot (316 plants m−2) were transplanted after 18 days after emergence into to 12 L pots. The treatments were: unfertilized soil, organic compost, organic compost +75 kg of N ha−1, applied as ammonium sulfate; and organic compost +75 kg N ha-1, applied as ammonium nitrate. The addition of organic compost to unfertilized soil increased the fresh yield. The application of inorganic N from the two sources in relation to organic compost treatment increased spinach fresh yield from 2.3 to 4.81 kg m−2 and shoot dry weight from 0.60 to 1,31 g plant−1. Levels of carotenoids also increased with inorganic N addition, producing higher values in plants grown with organic compost + ammonium nitrate (31.14 mg/100 g fresh weight). However, the addition of N led to a decrease in leaf-blade total phenols from 75 to 56 mg gallic acid equivalents/100mg fresh weight. The addition of inorganic N led to a dramatic decrease in leaf-blade ferric reducing antioxidant activity. This effect was higher with ammonium sulfate application. The application of organic compost and inorganic nitrogen had no influence on the petiole's phytochemical accumulation and antioxidant activity.